Kinship, dispersal and hantavirus transmission in bank and common voles - Deter, Julie; Chaval, Yannick; Galan, M.; Gauffre, B.; Morand, Serge; Henttonen, Heikki; Laakkonen, Juha; Voutilainen, Liina; Charbonnel, Nathalie; Cosson, Jean-François (Archives of Virology, 2008)
Contact: deter@supagro.inra.fr International audience Hantaviruses are among the main emerging infectious agents in Europe. Their mode of transmission in natura is still not well known. In particular, social features and behaviours could be crucial for understanding the persistence and the spread of hantaviruses in rodent populations. Here, we investigated the importance of kinclustering and dispersal in hantavirus transmission by combining a fine-scale spatiotemporal survey (4 km2) and a population genetics approach. Two specific host-hantavirus systems were identified and monitored: the bank vole Myodes, earlier Clethrionomys glareolus––Puumala virus and the common vole Microtus arvalis—Tula virus. Sex, age and landscape characteristics significantly influenced the spatial distribution of infections in voles. The absence of temporal stability in the spatial distributions of viruses suggested that dispersal is likely to play a role in virus propagation. Analysing vole kinship from microsatellite markers, we found that infected voles were more closely related to each other than non-infected ones. Winter kin-clustering, shared colonies within matrilineages or delayed dispersal could explain this pattern. These two last results hold, whatever the host-hantavirus system considered. This supports the roles of relatedness and dispersal as general features for hantavirus transmission.